Sexual Dysfunction in Epileptic Men - Nikoobakht, Mohammadreza; Motamedi, Mahmood; Orandi, Amirhossein; Meysamie, Alipasha; Emamzadeh, Ala (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to evaluate the frequency of sexual dysfunction among epileptic patients. Materials and Methods: Eighty married men between 22 and 50 years with a confirmed diagnosis of epilepsy were enrolled in this study. Patients with other neurological diseases, hypertension, cardiovascular diseases, diabetes mellitus, underlying urogenital diseases, and impaired general health status were excluded. Furthermore, those with mental health problems were identified by the standardized General Health Questionnaire-28 and were excluded. Demographic and clinical characteristics of the disease were evaluated, and sexual function was assessed by the self-administered questionnaire of the International Index of Erectile Function-15 (IIEF-15). Results: Of 80 patients, 34 (42.5%) had erectile dysfunction. There were no differences between the patients in the 3 age groups in the IIEF scores. Type of seizure had a significant correlation with erectile function score (P = .008). None of the IIEF domains scores were different between the patients with controlled epilepsy and those with uncontrolled epilepsy during the previous 6 months. However, frequency of epileptic seizures (before treatment) correlated with the scores for erectile function (r = 0.31; P = .005), orgasmic function (r = 0.23; P = .04), and sexual desire (r = 0.24; P = .03). Conclusion: It seems that the main aspects of sexual activity such as erectile function, orgasmic function, and sexual desire are frequently impaired in epileptic patients. Our findings were also indicative of a higher risk of sexual dysfunction in patients with partial seizures.